Brunei Darussalam : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2013)
The report gives statistical data on nominal GDP by economic activity and expenditure, real GDP by economic activity and expenditure, oil and gas production and sales figures, employment by government sector and private sector, consumer price index, composition of government revenue, expenditure and budget balance, central bank survey, depository bank survey, commercial bank loans, financial soundness indicators, Sukuk outstanding and yield, private investment by sector, export and import commodities and countries involved, and FDI of Brunei Darussalam.